STRATEGI PENGEMBANGAN WILAYAH BERBASIS POTENSI SEKTOR UNGGULAN KABUPATEN BONE BOLANGO - Srihantuti Paramata; Helmina Yaluminah (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to identify potential sectors and leading sectors of Bone Bolango Regency and identify changes in the base sector which will be prioritized as leading sectors that become potential drivers of development in Bone Bolango Regency. This study uses a quantitative approach and the data source used is secondary data for the last 5 years (2015-2019). The analytical tools used are shift share analysis (SSA) and request question (LQ). The results showed that the regional potential-based regional development strategy in Bone Bolango Regency had not been implemented optimally. The results of the analysis of the potential of the regional superior sector were quite supportive of the regional development process. The economic potential of Bone Bolango Regency can be seen from the basic sector owned which consists of 10 sectors or business fields, respectively: 1) Mining and Quarrying, 2) Manufacturing Industry, 3) Construction, 4) Wholesale and Retail Trade, 5) Real Estate Estate, 6) Corporate Services, 7) Government Administration, 8) Education Services, 9) Health Services, and 10) Other Services. The non-base sector of Bone Bolango Regency consists of 7 sectors or respective business fields; 1) Agriculture, 2) Procurement of Electricity and Gas, 3) Transportation and Warehousing, 4) Procurement of Water, Garbage, and Waste, 5) Provision of Accommodation and Food and Drink, 6) Information and Communication, and 7) Financial and Insurance Services